Method for testing casting fluidity of multi-principal-element iron-based medium-entropy alloy

By using vibration and high-pressure compression methods in the casting fluidity test of multi-main iron-based medium entropy alloys, the problem of insufficient testing accuracy is solved, and the accuracy and repeatability of the test data are significantly improved, providing reliable support for the fluidity testing of multi-main entropy alloys.

CN120177289APending Publication Date: 2025-06-20XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510358867.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

When testing the casting fluidity of multi-main iron-based medium entropy alloys, the test accuracy is insufficient, resulting in low stability of the results, making it difficult to accurately reflect its actual filling ability in complex thin-walled structures.

Method used

The sand-shaped layer is vibrated with a vibration frequency of 50-70Hz, and the sand-shaped layer is pressed with a pressure of 0.8-1.2MPa to form a test device with precisely controlled compactness between 1.6-1.8g/cm3 to improve the finish of the cavity surface.

Benefits of technology

It significantly improves the accuracy and repeatability of the test data, solves the problem of fluidity test distortion caused by poor sand uniformity and rough surface, and provides reliable support for the fluidity testing of multi-main mid-entropy alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120177289A_ABST
    Figure CN120177289A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-principal-element iron-based medium-entropy alloy casting fluidity testing method which comprises the following steps: respectively filling molding sand into a first sand mold layer, a second sand mold layer and a third sand mold layer, and putting a single-spiral metal sample model into the third sand mold layer; the first sand mold layer, the second sand mold layer and the third sand mold layer are vibrated, and the vibration frequency is 50-70 Hz; overlapping the vibrated first sand mold layer, second sand mold layer and third sand mold layer to obtain a sand mold; wherein the third sand mold layer is arranged at the bottommost layer; and the sand mold is pressed, the pressing pressure ranges from 0.8 MPa to 1.2 MPa, and after pressing is completed, the testing device for the casting fluidity of the multi-principal-element iron-based medium-entropy alloy is obtained. The problems that an existing testing method is insufficient in testing precision and low in stability are solved, and reliable support is provided for testing the fluidity of the entropy alloy in the multi-principal element for the diesel engine cylinder cover.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of the casting fluidity test of medium-entropy alloys, and particularly relates to a method for testing the casting fluidity of a multi-principal-element iron-based medium-entropy alloy. Background Art

[0002] With the rapid development of high-power diesel engines towards high compression ratios, high injection pressures, and high combustion pressures, traditional cast iron and aluminum alloy cylinder heads can no longer meet the comprehensive requirements of high strength, high heat resistance, and fatigue resistance. Multi-principal-element iron-based medium-entropy alloys (such as the Fe-Ni-Al system) have shown excellent specific strength, high-temperature creep resistance, and microstructural stability due to their unique composition design, and have become a key development direction for new low-density heat-resistant cylinder head materials. However, the cylinder head has a complex structure, including thin-walled airways, precision cooling water channels, and a cavity structure with variable curvatures, which poses extremely high requirements for the filling ability of the multi-principal-element iron-based medium-entropy alloy melt, and the filling ability is usually characterized by fluidity.

[0003] Currently, the spiral-line fluidity test method is widely used in the evaluation of metal fluidity. By injecting molten alloy into a test device and measuring the length of the casting fluidity test specimen after solidification, quantitative analysis can be achieved. However, for multi-principal-element iron-based medium-entropy alloys used in diesel engine cylinder heads, this method has significant limitations: the lack of test accuracy leads to low result stability, and it is difficult to accurately reflect the actual filling ability of multi-principal-element iron-based medium-entropy alloys used in diesel engine cylinder heads in complex thin-walled structures. Summary of the Invention

[0004] The purpose of the present invention is to provide a method for testing the casting fluidity of a multi-principal-element iron-based medium-entropy alloy to improve the test accuracy of the fluidity of multi-principal-element iron-based medium-entropy alloys used in diesel engine cylinder heads.

[0005] The present invention adopts the following technical solutions:

[0006] A method for testing the casting fluidity of a multi-principal-element iron-based medium-entropy alloy includes the following steps:

[0007] Fill molding sand into the first sand mold layer, the second sand mold layer, and the third sand mold layer respectively, and place a single-spiral metal specimen model in the third sand mold layer;

[0008] Vibrate the first sand mold layer, the second sand mold layer, and the third sand mold layer respectively, and the vibration frequency is 50 - 70 Hz;

[0009] Stack the vibrated first sand mold layer, the second sand mold layer, and the third sand mold layer to obtain a sand mold; wherein, the third sand mold layer is placed at the bottom layer;

[0010] Press the sand mold, and the pressing pressure is 0.8 - 1.2 MPa. After pressing, a test device for the casting fluidity of a multi-principal-element iron-based medium-entropy alloy is obtained.

[0011] Further, by mass percentage, the molding sand includes: raw sand: 85 - 90%, bentonite: 5 - 8%, water: 3 - 5%, and pulverized coal: 2 - 5%.

[0012] Further, before filling the molding sand into the first sand mold layer, the second sand mold layer, and the third sand mold layer respectively, it includes:

[0013] Preparing a single - helix metal specimen model by 3D printing method.

[0014] Further, a bump is arranged every 50 mm on the single - helix metal specimen model.

[0015] Further, after obtaining the test device for the casting fluidity of the multi - principal - element iron - based medium - entropy alloy, it includes:

[0016] Melting the multi - principal - element iron - based medium - entropy alloy and then refining it.

[0017] Further, after melting the multi - principal - element iron - based medium - entropy alloy and then refining it, it includes:

[0018] Performing a pre - heating treatment on the test device, and the temperature of the pre - heating treatment is 150 - 200 °C.

[0019] Further, after performing the pre - heating treatment on the test device, it includes:

[0020] Pouring the refined multi - principal - element iron - based medium - entropy alloy into the pre - heated test device, the pouring temperature is 1400 - 1500 °C, the ambient temperature is 18 - 40 °C, and the relative humidity is 30% - 65%.

[0021] Further, after pouring the refined multi - principal - element iron - based medium - entropy alloy into the pre - heated test device, it includes:

[0022] After pouring, it is naturally cooled to obtain a casting fluidity test specimen; wherein, the time of natural cooling is 1 - 1.5 h.

[0023] Further, after obtaining the casting fluidity test specimen, it includes:

[0024] Measuring the length of the casting fluidity test specimen, and then evaluating the casting fluidity of the multi - principal - element iron - based medium - entropy alloy.

[0025] The beneficial effects of the present invention are: Under the condition that the vibration frequency is 50 - 70 Hz, the first sand mold layer, the second sand mold layer, and the third sand mold layer are vibrated respectively, and the sand mold obtained after vibration is pressed with a pressure of 0.8 - 1.2 MPa; under the synergistic action of vibration and pressing, the sand mold compactness is accurately controlled at 1.6 - 1.8 g / cm 3, meanwhile, the surface finish of the cavity is improved (Ra≤6.3μm). The parameter combination of vibration and pressing solves the problem of distorted fluidity test caused by poor uniformity and rough surface of the sand mold in the prior art, significantly improves the accuracy and repeatability of the test data, and provides reliable support for the fluidity test of the multi-principal element medium-entropy alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a flowchart of the method of the present invention;

[0027] Figure 2 is a drawing of the lower sand box in Embodiments 1-3 of the present invention;

[0028] Figure 3 is a drawing of the test device in Embodiments 1-3 of the present invention;

[0029] Figure 4 is a drawing of the casting fluidity test specimen obtained in Embodiment 1 of the present invention;

[0030] Figure 5 is a drawing of the casting fluidity test specimen obtained in Embodiment 2 of the present invention;

[0031] Figure 6 is a drawing of the casting fluidity test specimen obtained in Embodiment 3 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0032] The present invention will be described in detail below with reference to the drawings and specific embodiments.

[0033] A method for testing the casting fluidity of a multi-principal element iron-based medium-entropy alloy, as Figure 1 shown, includes the following steps:

[0034] S110, filling molding sand into the first sand mold layer, the second sand mold layer and the third sand mold layer respectively, and placing a single spiral metal specimen model into the third sand mold layer.

[0035] Among them, the molding sand, by mass percentage, includes: silica sand: 85-90%, bentonite: 5-8%, water: 3-5%, pulverized coal: 2-5%.

[0036] Compared with common resin sands, sodium silicate sands, and coated sands, the molding sand ratio selected in the present invention has the advantages of low cost, environmental friendliness, and good renewability. The green sand with bentonite obtained using the raw materials and ratio of the present invention has excellent comprehensive properties. The addition of bentonite can provide good dry and wet strengths, reducing the risk of mold collapse during the molding process; the voids between silica sand particles cooperate with an appropriate amount of moisture, reducing porosity defects and having good air permeability; pulverized coal forms a reducing atmosphere and a bright carbon layer at high temperatures, effectively avoiding the adhesion of molten metal to the sand mold, with a remarkable anti-adhesion effect, improving the surface finish of the casting fluidity test specimen, and making the surface finish of the obtained casting fluidity test specimen closer to that of the diesel engine cylinder head manufactured using it.

[0037] S120, vibrate the first sand mold layer, the second sand mold layer, and the third sand mold layer respectively, with a vibration frequency of 50 - 70 Hz.

[0038] S130, stack the vibrated first sand mold layer, second sand mold layer, and third sand mold layer to obtain a sand mold; wherein, the third sand mold layer is placed at the bottommost layer.

[0039] S140, press the sand mold, with a pressing pressure of 0.8 - 1.2 MPa. After pressing is completed, a test device for the casting fluidity of the multi-principal element iron-based medium entropy alloy is obtained.

[0040] The casting static pressure of the traditional test device is 0.3 - 0.6 MPa, mainly relying on manual experience for adjustment, with large fluctuations. Generally, simple layered sand filling is used, resulting in uneven compactness and too large surface roughness. Through the synergistic effect of high-pressure pressing (0.8 - 1.2 MPa) and layered vibration (3 - 4 layers, 50 - 70 Hz), the present invention accurately controls the compactness of the test device at 1.6 - 1.8 g / cm 3 , while improving the surface finish of the cavity (Ra ≤ 6.3 μm). Compared with the prior art, this parameter combination solves the problem of distorted fluidity test caused by poor uniformity and rough surface of the test device, significantly improving the accuracy and repeatability of test data, and providing reliable support for the fluidity test of the multi-principal element medium entropy alloy used in diesel engine cylinder heads.

[0041] Before filling the molding sand into the first sand mold layer, the second sand mold layer, and the third sand mold layer respectively, it includes:

[0042] Prepare a single spiral metal specimen model using 3D printing, with a bump set every 50 mm on the single spiral metal specimen model.

[0043] The existing preparation method of the single - helix metal specimen model mainly involves fabricating the matrix of the single - helix metal specimen model through casting, then performing numerical control machining on it to ensure the dimensional accuracy of the single - helix metal specimen model, and finally conducting surface treatment on it to reduce the flow resistance during the casting process. Due to the complex structure of the diesel engine cylinder head, which includes thin - wall airways, precision cooling water channels, and a cavity structure with variable curvatures, therefore, the 3D printing method utilized in the present invention can better control the accuracy of the single - helix metal specimen model, quickly verify the feasibility of parameter design, reduce the preparation process of the single - helix metal specimen model, shorten the processing cycle, and lower the processing cost.

[0044] A bump is set every 50 mm on the single - helix metal specimen model. During the modeling process, corresponding concave points will be formed on the testing device, and corresponding convex points will be formed on the obtained casting fluidity test specimen. The length of the casting fluidity test specimen can be quickly calculated through the convex points.

[0045] After obtaining the testing device for the casting fluidity of the multi - principal - element iron - based medium - entropy alloy, it includes:

[0046] The multi - principal - element iron - based medium - entropy alloy is melted and then refined.

[0047] The testing device is pre - heated, and the pre - heating temperature is 150 - 200 °C.

[0048] The refined multi - principal - element iron - based medium - entropy alloy is poured into the pre - heated testing device. The pouring temperature is 1400 - 1500 °C, the ambient temperature is 18 - 40 °C, and the relative humidity is 30% - 65%.

[0049] After pouring, it is naturally cooled to obtain the casting fluidity test specimen; among them, the natural cooling time is 1 - 1.5 h.

[0050] The length of the casting fluidity test specimen is measured, and then the casting fluidity of the multi - principal - element iron - based medium - entropy alloy is evaluated.

[0051] In the prior art, the pre - heating temperature of the green sand is 100 - 200 °C, and the purpose is to remove the surface moisture. Since too high a temperature may cause too low a moisture content in the testing device and a decrease in strength, while too low a temperature is not conducive to the testing of alloy fluidity and the fluidity test value is on the low side. At the same time, the multi - principal - element iron - based medium - entropy alloy to be tested in the present invention is applied to the manufacture of diesel engine cylinder heads. The diesel engine cylinder head has a complex structure, including thin - wall airways, precision cooling water channels, and a cavity structure with variable curvatures, which puts extremely high requirements on the filling ability of the multi - principal - element iron - based medium - entropy alloy melt and even higher requirements on the alloy fluidity. Therefore, the selected pre - heating temperature range of the testing device in the present invention is 150 - 200 °C.

[0052] The liquidus temperature of the multi-principal element iron-based medium entropy alloy is usually higher than 1400 °C, while the traditional casting temperature of cast iron is 1300 - 1400 °C. This temperature range cannot meet the requirement of complete liquid flow for the application of the multi-principal element iron-based medium entropy alloy in the manufacture of diesel engine cylinder heads. The set temperature of 1450 °C in the present invention can ensure that the multi-principal element iron-based medium entropy alloy is in a super-liquid state, that is, 50 - 100 °C higher than the liquidus line, avoiding the fluidity deviation caused by premature solidification, and being more suitable for the manufacture of diesel engine cylinder heads.

[0053] The ambient temperature of the present invention is controlled at 18 - 40 °C, covering the high-temperature environment from normal temperature to summer, ensuring the applicability of the test method in different regions and seasons, and avoiding the non-repeatability of data caused by environmental fluctuations.

[0054] Since too high humidity will cause the test device to absorb moisture, a large amount of water vapor is likely to be generated during casting, leading to pores; too low humidity may cause the sand mold to become brittle and there is a risk of sand wash. Therefore, the relative humidity in the present invention is controlled at 30 - 65%.

[0055] The cooling time of traditional cast iron / steel is too long, generally 2 - 4 h. If the multi-principal element iron-based medium entropy alloy of the present invention also adopts this temperature, it may cause the aggravation of grain boundary segregation of the medium entropy alloy due to long-term high-temperature exposure; while the rapid cooling of aluminum alloy is less than 15 minutes, which cannot meet the phase change requirements of the multi-principal element iron-based medium entropy alloy. Therefore, the selected cooling time of 1 - 1.5 h in the present invention accurately covers the sensitive temperature range of the multi-principal element iron-based medium entropy alloy, that is, from 1450 °C to 200 °C.

[0056] Example 1

[0057] Test Fe under different vibration frequencies 59 Ni 30 Al 11 The specific process of the casting fluidity of the medium entropy alloy includes:

[0058] Step 1: Prepare a single-helix metal specimen model by 3D printing method, and a bump is set every 50 mm on the single-helix metal specimen model.

[0059] Step 2: Fill the molding sand into the first sand mold layer, the second sand mold layer and the third sand mold layer respectively, and place the single-helix metal specimen model into the third sand mold layer;

[0060] Vibrate the first sand mold layer, the second sand mold layer and the third sand mold layer respectively, and the vibration frequency is 50 Hz;

[0061] Overlap and place the vibrated first sand mold layer, the second sand mold layer and the third sand mold layer to obtain a sand mold; among them, the third sand mold layer is placed at the bottom layer;

[0062] Press the sand mold with a pressure of 1 MPa. After the pressing is completed, spray and brush the coating on the cavity of the sand mold to obtain a test device for the casting fluidity of the multi-principal-component iron-based medium-entropy alloy.

[0063] Among them, the molding sand, by mass percentage, includes: raw sand: 90%, bentonite: 5%, water: 3%, and pulverized coal: 2%.

[0064] Step 3: Melt the multi-principal-component iron-based medium-entropy alloy and then refine it;

[0065] Conduct preheating treatment on the test device at a temperature of 175 °C;

[0066] Pour the refined multi-principal-component iron-based medium-entropy alloy into the preheated test device. The pouring temperature is 1450 °C, the ambient temperature is 30 °C, and the relative humidity is 50%;

[0067] After the pouring is completed, let it cool naturally to obtain a casting fluidity test specimen; among them, the natural cooling time is 1.5 h;

[0068] Measure the length of the casting fluidity test specimen, and then evaluate the casting fluidity of the multi-principal-component iron-based medium-entropy alloy.

[0069] Example 2

[0070] The specific steps of this example are the same as those of Example 1, except that:

[0071] The vibration frequency in Step 2 is 60 Hz.

[0072] Example 3

[0073] The specific steps of this example are the same as those of Example 1 and Example 2, except that:

[0074] The vibration frequency in Step 2 is 70 Hz.

[0075] As Figure 2 and Figure 3 shown, it is a physical diagram of the test device in Examples 1-3. Figure 2 is the lower sand box, and the sand mold is in the shape of a complete single-spiral metal specimen printed by 3D; Figure 2 is a diagram of the test device after closing the mold. The sunken area at the top is the gate part, which is used to guide the molten multi-principal-component iron-based medium-entropy alloy to enter the test device at a suitable flow rate and direction, ensuring smooth filling and avoiding turbulence or splashing.

[0076] As Figure 4As shown, it is a casting fluidity test specimen obtained by using the test device modeled at a vibration frequency of 50 Hz in Example 1. It can be seen from the figure that the burrs of the casting fluidity test specimen modeled at a frequency of 50 Hz are obvious. This specimen has a total of 16 convex points, the length exceeding the last convex point is 25 mm, and the total length of the casting fluidity test specimen is 825 mm.

[0077] As Figure 5 shown, it is a casting fluidity test specimen obtained by using the test device modeled at a vibration frequency of 60 Hz in Example 2. It can be seen from the figure that the burrs of the casting fluidity test specimen modeled at a frequency of 60 Hz are significantly reduced. This specimen has a total of 14 convex points, the length exceeding the last convex point is 43 mm, and the total length of the casting fluidity test specimen is 843 mm.

[0078] As Figure 6 shown, it is a casting fluidity test specimen obtained by using the test device modeled at a vibration frequency of 70 Hz in Example 3. It can be seen from the figure that the burrs of the casting fluidity test specimen modeled at a frequency of 70 Hz are the least. This specimen has a total of 17 convex points, the length exceeding the last convex point is 2 mm, and the total length of the casting fluidity test specimen is 852 mm.

[0079] In summary, the present invention vibrates the first sand mold layer, the second sand mold layer, and the third sand mold layer respectively under the condition that the vibration frequency is 50 - 70 Hz, and presses the sand mold obtained after vibration with a pressure of 0.8 - 1.2 MPa; under the synergistic action of vibration and pressing, the sand mold compactness is accurately controlled at 1.6 - 1.8 g / cm 3 , while improving the surface finish of the cavity (Ra ≤ 6.3 μm). The parameter combination of vibration and pressing solves the problem of distorted fluidity test caused by poor sand mold uniformity and rough surface in the prior art, significantly improves the accuracy and repeatability of test data, and provides reliable support for the fluidity test of multi - principal - element medium - entropy alloys.

Claims

1. A method for testing casting fluidity of a multi-principal iron-based medium-entropy alloy, characterized in that: The following steps are involved: Filling the molding sand into the first sand molding layer, the second sand molding layer and the third sand molding layer respectively, and placing the single spiral metal sample model into the third sand molding layer; The first sand mold layer, the second sand mold layer and the third sand mold layer are vibrated respectively, with a vibration frequency of 50-70 Hz; The first sand mold layer, the second sand mold layer and the third sand mold layer after vibration are placed on top of each other to obtain a sand mold; wherein the third sand mold layer is placed at the bottom layer; The sand mold is pressed at a pressure of 0.8-1.2 MPa. After the pressing is completed, a testing device for casting fluidity of a multi-principal element iron-based medium entropy alloy is obtained.

2. A method for testing casting fluidity of a multi-principal iron-based medium entropy alloy according to claim 1, characterized in that: The molding sand comprises, by mass percentage, 85-90% of raw sand, 5-8% of bentonite, 3-5% of water, and 2-5% of coal powder.

3. A method for testing casting fluidity of a multi-principal iron-based medium entropy alloy according to claim 2, characterized in that: Before the molding sand is respectively filled into the first sand mold layer, the second sand mold layer and the third sand mold layer, the following steps are included: The single spiral metal specimen model is prepared by 3D printing.

4. A method for testing casting fluidity of a multi-principal iron-based medium entropy alloy according to claim 3, characterized in that: A convex point is arranged every 50 mm on the single spiral metal sample model.

5. A method for testing casting fluidity of a multi-principal iron-based medium entropy alloy according to claim 4, characterized in that: The testing device for the casting fluidity of multi-principal iron-based medium entropy alloys includes: The multi-principal iron-based medium entropy alloy is melted and then refined.

6. A method for testing casting fluidity of a multi-principal iron-based medium entropy alloy according to claim 5, characterized in that: After melting the multi-principal iron-based medium entropy alloy, the refining process includes: The test device is preheated at a temperature of 150-200°C.

7. A method for testing casting fluidity of a multi-principal iron-based medium entropy alloy according to claim 6, characterized in that: The test device is preheated and the method comprises: The refined multi-principal-element iron-based medium-entropy alloy is poured into a preheated test device at a pouring temperature of 1400-1500° C., an ambient temperature of 18-40° C., and a relative humidity of 30%-65%.

8. A method for testing casting fluidity of a multi-principal element iron-based medium entropy alloy according to claim 7, characterized in that: After pouring the refined multi-principal element iron-based medium entropy alloy into a preheated test device, the method further comprises: After pouring, the casting is cooled naturally to obtain a casting fluidity test sample; wherein, the natural cooling time is 1-1.5h.

9. A method for testing casting fluidity of a multi-principal iron-based medium entropy alloy according to claim 8, characterized in that: After obtaining the casting fluidity test sample, it includes: The length of the casting fluidity test sample is measured to evaluate the casting fluidity of the multi-principal element iron-based medium entropy alloy.